Why are Polish women diagnosed with invasive cervical cancer after negative cytology in the organized screening programme – a pilot reevaluation of negative Pap smears preceding diagnoses of interval cancers - Komerska, Katarzyna; Macios, Anna; Glińska, Patrycja; Olszewski, Włodzimierz; Didkowska, Joanna; Wojciechowska, Urszula; Kamiński, Michał F.; Nowakowski, Andrzej (Polish Journal of Pathology, 2021)
We have aimed to study reasons for reporting false-negative cytology results preceding diagnosis of interval cervical cancers (CC) in Poland. Data on all Pap smears collected in the organised screening in 2010-2015 were retrieved from the electronic database and linked with Polish National Cancer Registry (PNCR) data. False-negative results were defined as those sampled and assessed normal up to 3.5 years before diagnosis of invasive CC. False-negative slides were then seeded among twice as many randomly selected slides from the same lab and reviewed independently by three expert cytomorphologists. New diagnosis was established when experts agreed on a result. Of 48 selected false-negative slides, 1 case was diagnosed as a low-grade abnormality, 22 cases as a high-grade abnormalities, 3 cases as unsatisfactory for evaluation and 5 as no intraepithelial lesion of malignancy (NILM) by all three experts. There was no agreement in 17 cases. Percentages of agreement between experts was 64.6. Interobserver agreement rate was moderate with Fleiss’ κ values. Our pilot study indicates evaluation errors as the main reason of false-negative cytology preceding interval CC in the organized screening programme in Poland. True lack of abnormal cells on the slide is the next reason.